Oral Fluid Biomarkers for Peri-Implantitis: A Scoping Review - Supanat Lumbikananda; Supreda Suphanantachat Srithanyarat; Nikos Mattheos; Thanaphum Osathanon (Elsevier, 2024)
Peri-implantitis, a prevalent complication in dental implant therapy, poses a significant threat to long-term implant success. The identification of reliable biomarkers for the early detection and monitoring of peri-implantitis is crucial for timely intervention and improved treatment outcomes. Salivary and peri-implant sulcular fluid (PISF) biomarkers have become promising diagnostic tools in the field of implant dentistry. This scoping review aims to explore current studies in the literature on salivary and PISF biomarkers for peri-implantitis. A systematic search was conducted on 2 databases (PubMed and Scopus) to identify relevant studies published up to January 2023. A total of 86 articles were included, which underwent data extraction and analysis. Several biomarkers have been investigated in salivary and PISF samples for association with peri-implantitis. Investigations included a wide range of biomarkers, including inflammatory markers, matrix metalloproteinases and bone loss markers. The findings suggested that certain salivary and PISF biomarkers demonstrated potential in distinguishing healthy peri-implant conditions from peri-implantitis. Elevated levels of proinflammatory cytokines, such as interleukin-1β (IL-1β) and interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α), and matrix metalloproteinases, have been consistently associated with peri-implantitis. Additionally, alterations in bone loss markers have shown potential as indicators of disease progression and treatment response. In conclusion, this scoping review provides an overview of current knowledge on salivary and PISF biomarkers for peri-implantitis. The identified biomarkers are promising as noninvasive diagnostic tools for early detection, monitoring, and personalised management of peri-implantitis. Future studies should focus on establishing standardised protocols and conducting well-designed clinical trials to validate the diagnostic accuracy and clinical relevance of these biomarkers.